Urban Tree Planting: Implication on Sustainable Forest Management in Idi-Shin, Oyo State - E. B., Olawuyi (International Journal of Environment, Agriculture and Biotechnology, 2019)
The role of urban tree planting cannot be overemphasized as it design features in an urban area. However, the act of sustaining the continuous urban tree planting within and around the urban residents has become a challenge. Therefore, this study aim at investigating urban tree planting and it implication on sustainable forest management in Idin-shin area. Idi-shin was purposively selected for this study. A total of 2,963 people resides in the area and this was computed by projecting the population from the 1991census result obtained from the National Population Commission of Oyo state. Furthermore, 2.5% sampling intensity was used to select 74 respondents for the study. Primary data were collected with the aid of structured questionnaire. Data was analyzed using descriptive statistics and the logistic regression analysis. Results showed that majority of the respondents were between 32-50years with 32.4%, female (56.8%), married (50.0%), had tertiary education (54.1%) and most of them were civil servants (32.5%). It was also revealed that most (90.5%)of the respondents have idea on urban tree planting; this they(28.4%) got from watching television although these information comes on occasional basis (64.9%). Majority (56.8%) of the respondents have planted trees before and 81.9% of them confirmed that tree planting is not difficult, as such 72.7% agreed to engage in tree planting in their residence. Mango tree was the most common tree species planted in the residence of Idi-shin. Tree planted prevent wind (TPPW) and urban tree serve as shade (UTSS) was the most significant benefits of urban tree planting with odds-ratio of 3.18 and 2.13 respectively. Therefore, proper urban planning and community involvement in urban tree planting are important for sustainable forest management to be realized.